2017
DOI: 10.23974/ijol.2017.vol2.2.29
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Data Science Education in China from the LIS Perspective

Abstract: Abstract:The aim of this paper is to introduce the development of data science in higher education in China, including the policy and educational programs at various levels. We investigated the data science education of five LIS (Library and Information Studies) schools in China, using Fudan University's Data Management and Application Master's Program as an example for more specific information about the curriculum structure, course focus and teaching methods in data science education. The paper further descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…They found that most of these programmes were developed through collaboration between multiple schools and departments. In another study, Zhang et al (2017) investigate data science education in LIS schools in China by using the material available on their websites. In addition to the standard courses offered by Chinese LIS programmes, they found that these programmes involved various core courses related to data science, such as data management, data structure, database system principles, statistics, data analysis, data mining, algorithms, data repositories and cloud computing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that most of these programmes were developed through collaboration between multiple schools and departments. In another study, Zhang et al (2017) investigate data science education in LIS schools in China by using the material available on their websites. In addition to the standard courses offered by Chinese LIS programmes, they found that these programmes involved various core courses related to data science, such as data management, data structure, database system principles, statistics, data analysis, data mining, algorithms, data repositories and cloud computing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data science programmes have become popular in academia because of the growing demand for data science jobs, which have been described as ‘the sexiest job of the 21st century’ (Davenport and Patil, 2012). Different universities around the world have demonstrated their interest in data science education through the establishment of academic programmes at both the undergraduate and postgraduate levels, and there are a few universities that grant doctoral degrees in Data Science – for example, the PhD in Big Data and Data Science at the University of Washington and the PhD in Data Science at Fudan University in China (Zhang et al, 2017). Another PhD in Data Science is offered by New York University Shanghai in partnership with the New York University Graduate School of Arts and Science and the New York University Center for Data Science.…”
Section: Statement Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Data science is the study of tools, models, processes, techniques, analytics and technologies that can make data converted into knowledge, generate the value, and discover new knowledge via the collection, storage, transformation, visualization, analysis and management of data. To meet big data challenges, to adjust to the changes of social, economic and technological developments and to satisfy the needs for qualified graduates, universities in China have continuously offer degree programs and courses in data science and data science has been integrated into the programs and disciplines such as the discipline of library and information studies [17]. To cultivate qualified graduates in the age of big data, TCM colleges and universities should provide data science education in the teaching and research of TCM informatics.…”
Section: Data Science Education In the Tcm Informaticsmentioning
confidence: 99%
“…Feld: Empfehlungen, Vorbilder und RankingsÜber den ›lokalen‹ Kontext des akademischen Feldes hinaus sind die untersuchten Universitäten und Hochschulen in transnationale Wahrnehmungs-und Beobachtungsstrukturen eingebunden: Als neue Kategorie ist »Data Science« ein globales Phä-nomen, das sich in einer Vielzahl neuer Studiengänge rund um den Globus manifestiert(Demchenko et al 2016;Song & Zhu 2017;Stadelmann et al 2013;Tang & Sae-Lim 2016;Zhang et al 2017). Die Curricula sind in diesem Sinne nicht nur Stellungnahmen in einem nationalstaatlich konfigurierten Feld, sondern orientieren sich zudem an strukturell ähnlichen Positionen eines globalen Feldes der Hochschulbildung(Hedmo et al 2007; Zapp & Lerch 2020;Zapp & Ramirez 2019).…”
unclassified